A human capsaicin model to quantitatively assess salivary CGRP secretion. (July 2015) - van Oosterhout, WPJ; Schoonman, GG; Garrelds, IM; Danser, AHJ; Chan, KY; Terwindt, GM; Ferrari, MD; MaassenVanDenBrink, A
Background: Capsaicin induces the release of calcitonin gene-related peptide (CGRP) via the transient receptor potential channel V1 (TRPV1). The CGRP response after capsaicin application on the tongue might reflect the "activation state" of the trigeminal nerve, since trigeminal CGRP-containing vesicles are depleted on capsaicin application. We tested (i) the quantitative CGRP response after oral capsaicin application; (ii) the optimal concentration of red chili homogenate; and (iii) the day-to-day variability in this response. Methods: Saliva was collected for two consecutive days after oral application of eight capsaicin dilutions (red chili homogenates) of increasing concentrations in 13 healthy individuals. Effects of homogenate concentration were assessed. Consecutively, saliva was sampled after application of vehicle and undiluted homogenates. Results: CGRP secretion (pg/ml) increased dose-dependently with homogenate concentration ( p  < 0.001). CGRP levels were highest after application of nondiluted homogenate (vs. baseline: 13.3 (5.0) vs. 9.7 (2.9); p  = 0.003, as was total CGRP secretion in five minutes (pg) with undiluted (vs. baseline): 89.2 (44.1) vs. 14.1 (2.8); p  < 0.001. The dose-dependent response in CGRP was not affected by day ( p  = 0.14) or day*concentration ( p  = 0.60). Increase in CGRP (undiluted – baseline; pg/ml) did not differ between measurements on dose-finding ( p  = 0.67) and follow-up days ( p  = 0.46). Conclusion: Oral application of red chili homogenate is well tolerated and causes a dose-dependent CGRP release in saliva, without day-to-day effects in this response. This model could be used to noninvasively study the activation state of the trigeminal nerve innervating salivary glands.